Exploring the wicked problem dilemmas and driving mechanism of green transition: Evidence from the Yellow River Basin, China - Xie, Weiwei; Dong, Yaning; Jin, Tianlin (Frontiers in Earth Science, 2023)
The green transition of the Yellow River Basin (YRB) plays an important role in China’s economic and social development, as well as its ecological security. In view of the wicked problem dilemmas of development and emissions reduction in the YRB, this study theoretically and empirically examines the driving forces of its green transition. A six-sector green endogenous growth model reveals that low-carbon governance and innovation activities are the main drivers of green transition. Subsequently, a panel econometric model empirically explores how these drivers can solve the challenges of green transition. The findings are summarized as follows: low-carbon governance and innovative human and physical capital are key elements of green transition. The investment and innovation-driven periods regression results confirm that these elements drive green transition in the latter period. The regional heterogeneity show that drivers can promote green transition in highly developed areas. At the same time, with the inflow of innovative human capital, the promotion of low-carbon governance and innovative human capital to green transition has increased to an extent. Hence, combining the urban development stage and level to avoid a uniform policy may be key to the green transition in the YRB.